2010
DOI: 10.1097/md.0b013e3181d5453d
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Meningitis

Abstract: Staphylococcus aureus meningitis is a challenging disease and little is known about its epidemiology. There are no established management guidelines. We retrospectively reviewed the clinical information, bacteriologic data, and outcomes of all 33 patients with cerebrospinal fluid (CSF) cultures positive for S aureus seen at a single urban teaching hospital from 1999 to 2008. Pulsed-field gel electrophoresis (PFGE) and polymerase chain reaction for staphylococcal cassette chromosome mec (SCCmec), accessory gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…The initial source of hematogenous S. aureus meningitis is generally IE, pneumonia, or SSTI (788). The mortality rate for hematogenous S. aureus meningitis is higher (43 to 50%) than that occurring postsurgically (14 to 25%) (780,787). Among S. aureus meningitis cases, methicillin resistance has been increasing in recent years (786,(789)(790)(791).…”
Section: Meningitismentioning
confidence: 99%
See 3 more Smart Citations
“…The initial source of hematogenous S. aureus meningitis is generally IE, pneumonia, or SSTI (788). The mortality rate for hematogenous S. aureus meningitis is higher (43 to 50%) than that occurring postsurgically (14 to 25%) (780,787). Among S. aureus meningitis cases, methicillin resistance has been increasing in recent years (786,(789)(790)(791).…”
Section: Meningitismentioning
confidence: 99%
“…S. aureus meningitis may either arise by hematogenous spread from a non-CNS focus of infection or be secondary to neurosurgical intervention (785,786). Hematogenous S. aureus meningitis is usually community acquired (780,785) and, compared with postsurgical S. aureus meningitis, typically affects older individuals (mean age of 59 years versus 40 years; P ϭ 0.04) (787) with severe medical comorbidities such as diabetes or chronic kidney disease (780,787). The initial source of hematogenous S. aureus meningitis is generally IE, pneumonia, or SSTI (788).…”
Section: Meningitismentioning
confidence: 99%
See 2 more Smart Citations
“…Meningitis, caused by hematogenous spread, or acquired post-neurosurgery is of rising incidence and importance especially due to an increase in methicillin-resistant S. aureus (MRSA) strains in recent years. Although MRSA-mediated meningitis is rare, it has a high mortality rate, and is therefore a very serious disease (Aguilar et al, 2010; Pintado et al, 2012). Studies on the effect of S. aureus LTA on rat brain cells have shown that it can induce cerebellar neuronal cell death but only in the presence of glial cells.…”
Section: Other Bacteriamentioning
confidence: 99%